Manifesto for a Post-Critical Pedagogy - Hodgson, Naomi; Vlieghe, Joris; Zamojski, Piotr (punctum books, 2018)
The belief in the transformative potential of education has long underpinned critical educational theory. But its concerns have also been largely political and economic, using education as the means to achieve a better - or ideal - future state: of equality and social justice. Our concern is not whether such a state can be realized. Rather, the belief in the transformative potential of education leads us to start from the assumption of equality and to attend to what is "educational" about education. In Manifesto for a Post-Critical Pedagogy we set out five principles that call not for an education as a means to achieve a future state, but rather that make manifest those educational practices that do exist today and that we wish to defend. The Manifesto also acts as a provocation, as the starting point of a conversation about what this means for research, pedagogy, and our relation to our children, each other, and the world. Manifesto for a Post-Critical Pedagogy invites a shift from a critical pedagogy premised on revealing what is wrong with the world and using education to solve it, to an affirmative stance that acknowledges what is educational in our existing practices. It is focused on what we do and what we can do, if we approach education with love for the world and acknowledge that education is based on hope in the present, rather than on optimism for an eternally deferred future.